Positron Emission Tomography (PET) with 18F-FGA for Diagnosis of Myocardial Infarction in a Coronary Artery Ligation Model - Vibhudutta Awasthi; Hariprasad Gali; Andria F. Hedrick; Huining Da; Venkateswararao Eeda; Diwakar Jain (Molecular Imaging)
Location and extent of necrosis are valuable information in the management of myocardial infarction (MI). Methods. We investigated 2-deoxy-2-18F-fluoro glucaric acid (FGA), a novel infarct-avid agent, for positron emission tomography (PET) of MI. We synthesized FGA from commercially available 18F-fluoro-2-deoxy-2-D-glucose (FDG). MI was induced in mice by permanently occluding the left anterior descending coronary artery. Biodistribution of FGA was assessed 1 h after FGA injection (11 MBq). PET/CT was conducted 1 h, 6 h, 1 d, 3 d, and 4 d after MI. Subcellular compartment of FGA accumulation in necrosis was studied by tracing the uptake of biotin-labeled glucaric acid with streptavidin-HRP in H2O2-treated H9c2 cardiomyoblasts. Streptavidin-reactive protein bands were identified by LC-MS/MS. Results. We obtained a quantitative yield of FGA from FDG within 7 min (radiochemical purity>99%). Cardiac uptake of FGA was significantly higher in MI mice than that in control mice. Imaging after 1 h of FGA injection delineated MI for 3 days after MI induction, with negligible background signal from surrounding tissues. Myocardial injury was verified by tetrazolium staining and plasma troponin (47.63 pg/mL control versus 311.77 pg/mL MI). In necrotic H9c2 myoblasts, biotinylated glucaric acid accumulated in nuclear fraction. LC-MS/MS primarily identified fibronectin in necrotic cells as a putative high fidelity target of glucaric acid. Conclusion. FGA/PET detects infarct early after onset of MI and FGA accumulation in infarct persists for 3 days. Its retention in necrotic cells appears to be a result of interaction with fibronectin that is known to accumulate in injured cardiac tissue.